Lessons learned in cases of late preterm mortality in the Netherlands: Results from nationwide perinatal audits, a mixed method study - Ludovic Baauw; Ageeth N. Rosman; Thomas H. van den Akker (European Journal of Obstetrics & Gynecology and Reproductive Biology: X, 2023)
Objective: Assess improvable care factors in late preterm mortality, defined as death of a child during labour or in the first 28 days thereafter between 32 + 0 and 36 + 6 weeks gestation, in the Netherlands. Design: Perinatal audit has been coordinated and supported at the national level, with selection of nationwide audit themes, and audit sessions are performed at the local level across the country as multidisciplinary meetings with primary and secondary level health care professionals, organised in local perinatal cooperation units. In 2017–2019, late preterm mortality was such a theme. We compiled and systematically categorised all improvable care factors formulated during local audit meetings in a national perinatal audit database. Results: In total, 27 cases were discussed in local perinatal audits and analysed locally and at the national level. Altogether, 52 improvable care factors were identified. Most identified improvable care factors concerned inadequate foetal monitoring by cardiotocography during labour, factors related to care organisation, particularly unclarity around local assigning of responsibilities and work procedures, and poor communication between involved health care professionals especially in transfer of care. Conclusion: Several critical improvable care factors were identified through nationwide perinatal audit of late preterm deaths in the Netherlands.